The EC reaffirms the importance of the cotton initiative at Cancun - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
In his September 10th 2003 statement on the cotton initiative, EU Trade...